Building the Future of Tourism: Stakeholder Synergy in the Sustainability Transition in Sikka Regency, East Nusa Tenggara Province - Wisang, Paulus Nong; Rosalina Andriyani Ebang Pareira (Cita konsultindo, 2025)
Sustainable tourism development in the transdisciplinary era demands strategies that are not only environmentally friendly but also community-oriented. The sustainability transition has become a key issue in efforts to achieve sustainable development goals, particularly in the context of regional tourism. This study explores stakeholder engagement in the sustainability transition, analyses their perceptions, and designs a collaborative model for the implementation of sustainable tourism. Adopting a qualitative approach based on critical discourse analysis, this research gathers data from policy documents, reports, media articles, and in-depth interviews with local government officials, tourism industry actors, local communities, and NGOs. The findings indicate that the local government has initiated sustainability transition discourse through the revision of the tourism master plan. Although stakeholders exhibit a positive perception of sustainability, significant challenges remain, particularly in rural destinations that receive limited attention. Hence, this study proposes a stakeholder collaboration model that emphasises cross-sectoral synergy as a strategic step towards achieving sustainable tourism in Sikka Regency. This model is expected to enhance community participation, strengthen local capacities, and ensure that tourism development aligns with sustainability principles.